Pretty little liars - Shepard, Sara 1977- (New York HarperTempest, 2006)
When one of their tightly-knit group mysteriously disappears, four high school girls find their friendship difficult to maintain when they begin receiving taunting messages from someone who seems to know everything about their past and present secrets
1
Keywords: Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Fiction; Friendship -- Fiction; High schools -- Fiction; Mystery and detective stories; Schools -- Fiction; Secrets -- Fiction